Return Saham Ditinjau dari Manajemen Modal Kerja, Kebijakan Dividen, Free Cash Flow dan Profitabilitas - Alfiah Rizqi Sabrina; Nera Marinda Machdar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to understand and analyze theories that discuss the influence of working capital management, dividend policy, and free cash flow on stock returns with profitability as a moderating variable. Stock returns are investment benefits obtained by investors from invested capital, in the form of dividends and capital gains, namely the positive difference between the purchase and sale prices of shares. This study is based on grand theory, signal theory, and agency theory. The method used in this study is a literature review, by presenting theoretical studies, other explanatory variables, and previous research results. The results of the analysis show differences in findings related to the relationship between working capital management, dividend policy, and free cash flow on stock returns. Profitability as a moderating variable plays an important role, although there have been no consistent conclusions from the various studies reviewed. This study contributes to providing a deeper understanding to explain related phenomena and opens up opportunities for further research on this topic.